PENGARUH GAYA HIDUP DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPEDA PADA SITUASI COVID 19 DI KOTA MEDAN - Astuti, Rini; Hasbi, Muhammad (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This study aims to determine the effect of lifestyle and word of mouth on bicycle purchasing decisions in the Covid 19 situation in the city of Medan. This research is a type of qualitative research, and the data used in this study are data obtained based on data sources, namely: The data source used by the researcher is the primary data source. The sampling technique used was purposive sampling, purposive sampling was a sampling technique with certain considerations. The samples taken are based on questionnaires filled out by respondents or consumers who use bicycles, who can be met during the research. The analysis method used is multiple regression. The results showed that the Lifestyle variable had a negative and insignificant effect on purchasing decisions. The Word Of Mouth variable has a positive and significant effect on purchasing decisions.